Hydrophobic fluorosilicone microgel and preparation method thereof
By preparing hydrophobic fluorosilic microgels, using raw materials such as perfluorooctylethylacrylate to form a three-dimensional crosslinking network, the problems of anti-fouling, anti-fingerprint and insufficient adhesion of the microgel coating are solved, and the combination of high water contact angle and good adhesion is achieved.
Patent Information
- Application Number
- CN202510559725.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-07-08
AI Technical Summary
The existing microgel coatings have shortcomings in antifouling, fingerprint resistance, wear resistance and adhesion, and are difficult to meet the requirements of high water contact angle and good adhesion at the same time.
Perfluorooctylethylacrylate, functional components, acrylate monomers, trimethylolpropane triacrylate and azobisisobutyronitrile are used as raw materials to prepare hydrophobic fluorosilic microgels through emulsion polymerization, and fluorocarbon segments and active functional groups are introduced to form a three-dimensional crosslinking network structure.
It gives the coating good hardness, wear resistance and anti-fouling and fingerprint resistance, while improving adhesion to the substrate, balancing the contradiction between anti-fouling and adhesion.
Smart Images

Figure CN120271755A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material synthesis, and specifically relates to a hydrophobic fluorosilica microgel and a preparation method thereof. Background Art
[0002] Microgels are soft matter particles composed of a three-dimensional cross-linked polymer network. Under certain conditions, they have good physical and chemical properties. Therefore, microgels are widely used in fields such as coatings, catalyst carriers, and sensor devices, and are generally prepared by emulsion polymerization and solution polymerization. These two preparation methods each have their own advantages and disadvantages. The emulsion polymerization process is relatively stable and there will be no phenomena such as explosive polymerization, but a large amount of emulsifier is required in emulsion polymerization. After polymerization is completed, the emulsifier remains in the product, which has a certain impact on the product performance. Solution polymerization generally only contains polymerization monomers, solvents, and initiators, and the polymerization product is relatively pure, but the yield of microgels is generally low.
[0003] Since microgels have a three-dimensional cross-linked polymer network structure, they can endow the coating with good hardness and wear resistance. Patent CN117624485A prepared a microgel acrylic emulsion through a mono-vinyl unsaturated monomer, a hydroxyl functional monomer, a carboxyl functional monomer, and an emulsifier (sodium acrylamidopropyl sulfonate, allyl polyol ether sodium sulfate, etc.). This emulsion can be used in waterborne metal composite coatings including waterborne metal primers and waterborne topcoats.
[0004] Patent CN101870760A discloses a preparation method of a microgel resin and an ultraviolet curable anti-fouling coating prepared with the microgel resin. It prepared a microgel resin through isobornyl acrylate monomer, (meth)acrylic acid alkyl ester monomer, crosslinking agent, chain transfer agent, and photoinitiator. The polyacrylic resin prepared by this patent contains a certain amount of microgel structure, and through fluorine-containing monomers, the resin coating is given a certain anti-fouling performance. However, the microgel structure prepared by it does not have chemically active functional groups. In this way, the adhesion to some substrates is difficult to meet the adhesion requirements. Summary of the Invention
[0005] The purpose of the present invention is to provide a hydrophobic fluorosilica microgel and a preparation method thereof to solve the problems of poor high water contact angle (anti-fouling and anti-fingerprint performance), wear resistance, and adhesion of the coating proposed in the above background art.
[0006] To achieve the above object, the present invention provides the following technical solution: A hydrophobic fluorosilica microgel, comprising the following components in parts by weight: 3.54 - 8.96 parts of perfluorooctylethyl acrylate, 0.96 - 4.05 parts of functional component, 2.94 - 9.99 parts of methyl acrylate, 4.48 - 11.09 parts of butyl acrylate, 1.01 - 2.56 parts of trimethylolpropane triacrylate, 0.39 - 0.99 parts of azobisisobutyronitrile, and 65.0 - 85.0 parts of butyl acetate.
[0007] Preferably, the functional component is 2-isocyanatoethyl acrylate, and its parts by weight are 0.96 - 2.34 parts.
[0008] Preferably, the functional component is 3-(trimethoxysilyl)propyl acrylate, and its parts by weight are 1.64 - 4.05 parts.
[0009] A preparation method of a hydrophobic fluorosilica microgel, comprising the following steps:
[0010] S1. Mix perfluorooctylethyl acrylate and the functional component evenly to obtain premix I; mix the monofunctional monomer and the polyfunctional monomer evenly to obtain premix II; completely dissolve the initiator in the solvent to obtain premix III;
[0011] S2. Heat premix II to the reaction temperature under stirring conditions; then slowly dropwise add premix III thereto, adjust the dropping rate to keep the system temperature stable within the reaction temperature range; after the dropping is completed, keep the temperature at the reaction temperature for a period of time to obtain a primary prepolymer;
[0012] S3. Under stirring conditions, dropwise add premix I to the primary prepolymer obtained in step S2 to keep the system temperature stable at the reaction temperature; after the dropwise addition of premix I is completed, first keep the temperature at the reaction temperature for a period of time; then raise the temperature for a period of time; after the temperature-raising reaction time is completed, the predetermined product is obtained.
[0013] Preferably, in S1, the perfluorooctylethyl acrylate has a purity > 98%.
[0014] Preferably, in S1, the monofunctional monomer is one of methyl acrylate, methyl methacrylate, and n-butyl acrylate, with a purity of more than 97%.
[0015] Preferably, in S1, the polyfunctional monomer is one of pentaerythritol triacrylate and trimethylolpropane triacrylate, with a purity of more than 97%.
[0016] Preferably, the initiator in S1 is one of azobisisobutyronitrile and azobisisoheptonitrile, with a purity of more than 99%.
[0017] Preferably, the solvent in S1 is one of butyl acetate and dipropylene glycol dimethyl ether, with a purity of more than 99.5%.
[0018] Preferably, the addition amount of the solvent in S1 is 65%-85% of the total mass.
[0019] Preferably, the reaction temperature in step S2 is 65°C to 72°C, more preferably 68°C to 70°C, and the reaction time is 1.5 h - 2.5 h, more preferably 2.0 h.
[0020] Preferably, the reaction temperature in step S3 is 65°C to 72°C, more preferably 68°C to 70°C, and the holding reaction time is 5.0 h - 7.0 h, more preferably 6.0 h; the temperature for the temperature increase reaction is 90°C - 95°C, more preferably 92 - 93°C, and the reaction time is 2.5 h - 3.5 h, more preferably 3.0 h.
[0021] The application of the hydrophobic fluorosilica microgel in preparing an anti-fingerprint and anti-fouling coating. Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] 1. Through the microgel structure, the invention can endow the coating with good hardness and wear resistance.
[0023] 2. On the microgel structure, the present invention introduces fluorocarbon chain segments, which can endow the coating with good anti-fouling and anti-fingerprint properties.
[0024] 3. On the microgel structure, the present invention introduces functional components (isocyanate active functional groups or siloxane active groups), which can endow the coating with excellent adhesion to the substrate and balance the contradiction between anti-fouling and adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the structure of the isocyanated hydrophobic fluorosilica microgel of the present invention;
[0026] Figure 2 It is a schematic diagram of the water contact angle after the isocyanate hydrophobic fluorosilica microgel of the present invention is used for UV coating curing test;
[0027] Figure 3 It is a schematic diagram of the structure of the siloxanated hydrophobic fluorosilica microgel of the present invention;
[0028] Figure 4 It is a schematic diagram of the water contact angle after the siloxanated hydrophobic fluorosilica microgel of the present invention is used for UV coating curing test. DETAILED DESCRIPTION OF THE INVENTION
[0029] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0030] Example 1: Please refer to Figure 1 and Figure 2 , a preparation method of isocyanato-functionalized hydrophobic fluorosilicone microgel, comprising the following components in parts by weight:
[0031]
[0032] The isocyanato-functionalized hydrophobic fluorosilicone microgel is prepared by a method comprising the following steps:
[0033] S1. Mix 7.22 parts by weight of perfluorooctylethyl acrylate and 1.97 parts by weight of 2-isocyanatoethyl acrylate evenly to obtain a premix I; mix 7.20 parts by weight of methyl acrylate, 10.72 parts by weight of butyl acrylate and 2.06 parts by weight of trimethylolpropane triacrylate evenly to obtain a premix II; completely dissolve 0.90 part by weight of initiator azobisisobutyronitrile in 70.0 parts by weight of butyl acetate solvent to obtain a premix III;
[0034] S2. Heat the premix II to 68 °C - 70 °C under stirring conditions; then slowly dropwise add the premix III thereto, adjust the dropping rate to keep the system temperature stable at 68 °C - 70 °C; after the dropping is completed, keep the temperature at 68 °C - 70 °C and carry out a holding reaction for 2.0 h to obtain a primary prepolymer;
[0035] S3. Under stirring conditions, dropwise add the premix I to the primary prepolymer obtained in step S2 to keep the system temperature stable at 68 °C - 70 °C; after the premix I is completely dropped, first keep the temperature at 68 °C - 70 °C and hold for 6.0 h; then raise the temperature to 92 - 93 °C and react for 3.0 h; after the reaction time is completed, the isocyanato-functionalized hydrophobic fluorosilicone microgel is obtained.
[0036] Example 2: Please refer to Figure 1 and Figure 2 , a preparation method of isocyanato-functionalized hydrophobic fluorosilicone microgel, comprising the following components in parts by weight:
[0037]
[0038] The isocyanato-functionalized hydrophobic fluorosilicone microgel is prepared by a method comprising the following steps:
[0039] S1. Mix 8.59 parts by weight of perfluorooctylethyl acrylate and 2.34 parts by weight of 2-isocyanatoethyl acrylate evenly to obtain premix I; mix 9.99 parts by weight of methyl acrylate, 10.63 parts by weight of butyl acrylate and 2.46 parts by weight of trimethylolpropane triacrylate evenly to obtain premix II; completely dissolve 0.99 part by weight of initiator azobisisobutyronitrile in 65.0 parts by weight of butyl acetate solvent to obtain premix III;
[0040] S2. Heat premix II to 68 °C - 70 °C under stirring conditions; then slowly dropwise add premix III thereto, adjust the dropping rate to keep the system temperature stable at 68 °C - 70 °C; after the dropping is completed, keep the temperature at 68 °C - 70 °C and carry out a heat preservation reaction for 2.0 h to obtain a primary prepolymer;
[0041] S3. Under stirring conditions, dropwise add premix I to the primary prepolymer obtained in step S2 to keep the system temperature stable at 68 °C - 70 °C; after the dropping of premix I is completed, first keep the temperature at 68 °C - 70 °C and carry out a heat preservation for 6.0 h; then raise the temperature to 92 - 93 °C and react for 3.0 h; after the reaction time is completed, isocyanato-functionalized hydrophobic fluorosilica microgel is obtained.
[0042] Example 3: Please refer to Figure 1 and Figure 2 , a preparation method of isocyanato-functionalized hydrophobic fluorosilica microgel, comprising the following components in parts by weight:
[0043]
[0044] The isocyanato-functionalized hydrophobic fluorosilica microgel is prepared by a method comprising the following steps:
[0045] S1. Mix 3.54 parts by weight of perfluorooctylethyl acrylate and 0.96 part by weight of 2-isocyanatoethyl acrylate evenly to obtain premix I; mix 2.94 parts by weight of methyl acrylate, 6.13 parts by weight of butyl acrylate and 1.01 part by weight of trimethylolpropane triacrylate evenly to obtain premix II; completely dissolve 0.41 part by weight of initiator azobisisobutyronitrile in 85.0 parts by weight of butyl acetate solvent to obtain premix III;
[0046] S2. Heat premix II to 68 °C - 70 °C under stirring conditions; then slowly dropwise add premix III thereto, adjust the dropping rate to keep the system temperature stable at 68 °C - 70 °C; after the dropping is completed, keep the temperature at 68 °C - 70 °C and carry out a heat preservation reaction for 2.0 h to obtain a primary prepolymer;
[0047] S3. Under stirring conditions, add the pre-mixture I dropwise to the primary prepolymer obtained in step S2, and keep the system temperature stable at 68 °C to 70 °C; after the addition of the pre-mixture I is completed, first keep it warm at 68 °C to 70 °C for 6.0 h; then raise the temperature to 92 - 93 °C and react for 3.0 h; after the reaction time is completed, the isocyanated hydrophobic fluorosilica microgel is obtained.
[0048] Example 4: Please refer to Figure 1 and Figure 2 , a preparation method of an isocyanated hydrophobic fluorosilica microgel, comprising the following components in parts by weight:
[0049]
[0050]
[0051] The isocyanated hydrophobic fluorosilica microgel is prepared by a method comprising the following steps:
[0052] S1. Mix 6.26 parts by weight of perfluorooctylethyl acrylate and 1.71 parts by weight of 2-isocyanatoethyl acrylate evenly to obtain the pre-mixture I; mix 8.32 parts by weight of methyl acrylate, 6.20 parts by weight of butyl acrylate and 1.79 parts by weight of trimethylolpropane triacrylate evenly to obtain the pre-mixture II; completely dissolve 0.72 part by weight of the initiator azobisisobutyronitrile in 75.0 parts by weight of butyl acetate solvent to obtain the pre-mixture III;
[0053] S2. Heat the pre-mixture II to 68 °C to 70 °C under stirring conditions; then slowly add the pre-mixture III dropwise thereto, adjust the dropping rate to keep the system temperature stable at 68 °C to 70 °C; after the addition is completed, keep it warm and react at 68 °C to 70 °C for 2.0 h to obtain the primary prepolymer;
[0054] S3. Under stirring conditions, add the pre-mixture I dropwise to the primary prepolymer obtained in step S2, and keep the system temperature stable at 68 °C to 70 °C; after the addition of the pre-mixture I is completed, first keep it warm at 68 °C to 70 °C for 6.0 h; then raise the temperature to 92 - 93 °C and react for 3.0 h; after the reaction time is completed, the isocyanated hydrophobic fluorosilica microgel is obtained.
[0055] Experimental Example
[0056] The isocyanated hydrophobic fluorosilica microgels prepared in Example 1, Example 2, Example 3, and Example 4 were added to the following formulation at a weight ratio of 5% (calculated based on the solid content), and a blank test was used as the control group. They are represented by Experimental Example 1, Experimental Example 2, Experimental Example 3, Experimental Example 4, and Experimental Example 5 respectively, as shown in Table 1. After mixing all the materials evenly, they were coated on an untreated PET film with a thickness of 10 μm, baked in an oven at 60 °C for 2 min to remove the solvent, and then cured with a mercury lamp with an intensity of 500 mW / cm 2 for 10 seconds. Then, after standing at room temperature for 48 h, relevant performance tests were carried out.
[0057] Table 1
[0058]
[0059] The abrasion resistance, solid content, and adhesion were tested according to the methods of GB / T 23989-2023, GB / T 1725-2007, and GB / T 9286-1998 of the national standard, and the antifouling performance was tested by the method of measuring the water contact angle of the coating. The results are shown in Table 2.
[0060] Table 2
[0061]
[0062] It can be seen from the test results that the isocyanated hydrophobic fluorosilica microgel prepared by the present invention has a good effect on improving the abrasion resistance, adhesion, and antifouling property of the coating.
[0063] Example Five: Please refer to Figure 3 and Figure 4 , a preparation method of a siloxanated hydrophobic fluorosilica microgel, comprising the following components in parts by weight:
[0064]
[0065]
[0066] The siloxanated hydrophobic fluorosilica microgel is prepared by a method comprising the following steps:
[0067] S1. Mix 8.96 parts by weight of perfluorooctylethyl acrylate and 4.05 parts by weight of 3-(trimethoxysilyl)propyl acrylate evenly to obtain Premix I; mix 7.45 parts by weight of methyl acrylate, 11.09 parts by weight of butyl acrylate, and 2.56 parts by weight of trimethylolpropane triacrylate evenly to obtain Premix II; completely dissolve 0.89 part by weight of the initiator azobisisobutyronitrile in 65.0 parts by weight of butyl acetate solvent to obtain Premix III;
[0068] S2. Heat the premix II to 68°C - 70°C under stirring conditions; then slowly add the premix III dropwise thereto, adjust the dropping rate to keep the system temperature stable at 68°C - 70°C; after the dropping is completed, keep the temperature at 68°C - 70°C and carry out a heat preservation reaction for 2.0 h to obtain a primary prepolymer;
[0069] S3. Under stirring conditions, add the premix I dropwise to the primary prepolymer obtained in step S2 to keep the system temperature stable at 68°C - 70°C; after the premix I is completely added dropwise, first keep the temperature at 68°C - 70°C for heat preservation for 6.0 h; then raise the temperature to 105 - 107°C and react for 2.0 h; after the reaction time is completed, the siloxanized hydrophobic fluorosilica microgel is obtained.
[0070] Example VI: Please refer to Figure 3 and Figure 4 , a preparation method of a siloxanized hydrophobic fluorosilica microgel, comprising the following components in parts by weight:
[0071]
[0072]
[0073] The above-mentioned siloxanized hydrophobic fluorosilica microgel is prepared by a method comprising the following steps:
[0074] S1. Mix 6.03 parts by weight of perfluorooctylethyl acrylate and 2.73 parts by weight of 3 - trimethoxysilylpropyl acrylate uniformly to obtain premix I; mix 5.51 parts by weight of methyl acrylate, 8.20 parts by weight of butyl acrylate and 1.90 parts by weight of trimethylolpropane triacrylate uniformly to obtain premix II; completely dissolve 0.65 parts by weight of initiator azobisisobutyronitrile in 75.0 parts by weight of butyl acetate solvent to obtain premix III;
[0075] S2. Heat the premix II to 68°C - 70°C under stirring conditions; then slowly add the premix III dropwise thereto, adjust the dropping rate to keep the system temperature stable at 68°C - 70°C; after the dropping is completed, keep the temperature at 68°C - 70°C and carry out a heat preservation reaction for 2.0 h to obtain a primary prepolymer;
[0076] S3. Under stirring conditions, add the premix I dropwise to the primary prepolymer obtained in step S2 to keep the system temperature stable at 68°C - 70°C; after the premix I is completely added dropwise, first keep the temperature at 68°C - 70°C for heat preservation for 6.0 h; then raise the temperature to 105 - 107°C and react for 2.0 h; after the reaction time is completed, the siloxanized hydrophobic fluorosilica microgel is obtained.
[0077] Example VII: Please refer to Figure 3 and Figure 4, A preparation method of a siloxanized hydrophobic fluorosilica microgel, comprising the following components in parts by weight:
[0078]
[0079] The above-mentioned siloxanized hydrophobic fluorosilica microgel is prepared by a method comprising the following steps:
[0080] S1. Mix 3.63 parts by weight of perfluorooctylethyl acrylate and 1.64 parts by weight of 3-(trimethoxysilyl)propyl acrylate evenly to obtain premix I; mix 3.61 parts by weight of methyl acrylate, 4.48 parts by weight of butyl acrylate and 1.24 parts by weight of trimethylolpropane triacrylate evenly to obtain premix II; completely dissolve 0.39 part by weight of initiator azobisisobutyronitrile in 85.0 parts by weight of butyl acetate solvent to obtain premix III;
[0081] S2. Heat premix II to 68 °C - 70 °C under stirring conditions; then slowly dropwise add premix III thereto, adjust the dropping rate to keep the system temperature stable at 68 °C - 70 °C; after the dropping is completed, keep the temperature at 68 °C - 70 °C and carry out a heat preservation reaction for 2.0 h to obtain a primary prepolymer;
[0082] S3. Under stirring conditions, dropwise add premix I to the primary prepolymer obtained in step S2 to keep the system temperature stable at 68 °C - 70 °C; after the dropwise addition of premix I is completed, first keep the temperature at 68 °C - 70 °C and carry out a heat preservation for 6.0 h; then raise the temperature to 105 - 107 °C and react for 2.0 h; after the reaction time is completed, the siloxanized hydrophobic fluorosilica microgel is obtained.
[0083] Example VIII: Please refer to Figure 3 and Figure 4 , A preparation method of a siloxanized hydrophobic fluorosilica microgel, comprising the following components in parts by weight:
[0084]
[0085] The above-mentioned siloxanized hydrophobic fluorosilica microgel is prepared by a method comprising the following steps:
[0086] S1. Mix 7.63 parts by weight of perfluorooctylethyl acrylate and 3.45 parts by weight of 3-(trimethoxysilyl)propyl acrylate evenly to obtain premix I; mix 6.34 parts by weight of methyl acrylate, 9.43 parts by weight of butyl acrylate and 2.40 parts by weight of trimethylolpropane triacrylate evenly to obtain premix II; completely dissolve 0.76 part by weight of initiator azobisisobutyronitrile in 70.0 parts by weight of butyl acetate solvent to obtain premix III;
[0087] S2. Heat the premix II to 68°C - 70°C under stirring conditions; then slowly dropwise add the premix III thereto, adjust the dropping rate to keep the system temperature stable at 68°C - 70°C; after the dropping is completed, keep the temperature at 68°C - 70°C and carry out an insulation reaction for 2.0 h to obtain the primary prepolymer;
[0088] S3. Under stirring conditions, dropwise add the premix I to the primary prepolymer obtained in step S2 to keep the system temperature stable at 68°C - 70°C; after the dropping of the premix I is completed, first keep the temperature at 68°C - 70°C and carry out an insulation for 6.0 h; then raise the temperature to 105 - 107°C and react for 2.0 h; after the reaction time is completed, the siloxanized hydrophobic fluorosilica microgel is obtained.
[0089] Experimental Examples
[0090] Add the siloxanized hydrophobic fluorosilica microgels prepared in Example 5, Example 6, Example 7, and Example 8 to the following formula at a weight ratio of 5% (calculated based on the solid content), and use a blank test as a control group. They are represented by Experimental Example 1, Experimental Example 2, Experimental Example 3, Experimental Example 4, and Experimental Example 5 respectively, as shown in Table 1. After mixing all the materials evenly, coat them on the untreated PET film with a thickness of 10 μm, bake in an oven at 60°C for 2 min to remove the solvent, and then cure with a mercury lamp with an intensity of 500 mW / cm 2 for 10 seconds. Then, after standing at room temperature for 48 h, carry out relevant performance tests.
[0091] Table 1
[0092]
[0093] The abrasion resistance, solid content, and adhesion are tested according to the methods of GB / T 23989 - 2023, GB / T 1725 - 2007, and GB / T 9286 - 1998 of the national standard, and the antifouling performance is tested by the method of measuring the water contact angle of the coating. The results are shown in Table 2.
[0094] Table 2
[0095]
[0096] It can be seen from the test results that the siloxanized hydrophobic fluorosilica microgel prepared by the present invention has a good effect on improving the abrasion resistance, adhesion, and antifouling property of the coating.
[0097] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A hydrophobic fluorosilica microgel, characterized in that, Comprising: The following components in parts by weight: 3.54 - 8.96 parts of perfluorooctylethyl acrylate, 0.96 - 4.05 parts of functional component, 2.94 - 9.99 parts of methyl acrylate, 4.48 - 11.09 parts of butyl acrylate, 1.01 - 2.56 parts of trimethylolpropane triacrylate, 0.39 - 0.99 parts of azobisisobutyronitrile, 65.0 - 85.0 parts of butyl acetate.
2. The hydrophobic fluorosilica microgel according to claim 1, wherein: The functional component is 2 - isocyanatoethyl acrylate, and its parts by weight are 0.96 - 2.34 parts.
3. The hydrophobic fluorosilica microgel according to claim 1, wherein: The functional component is 3 - (trimethoxysilyl)propyl acrylate, and its parts by weight are 1.64 - 4.05 parts.
4. The preparation method of a hydrophobic fluorosilica microgel according to claim 1, characterized in that, Including the following steps: S1. Mix perfluorooctylethyl acrylate and the functional component evenly to obtain premix I; mix the monofunctional monomer and the polyfunctional monomer evenly to obtain premix II; completely dissolve the initiator in the solvent to obtain premix III; S2. Heat premix II to the reaction temperature under stirring conditions; then slowly dropwise add premix III thereto, adjust the dropping rate to keep the system temperature stable within the reaction temperature range; after the dropping is completed, keep the temperature at the reaction temperature for a period of time to obtain a primary prepolymer; S3. Under stirring conditions, dropwise add premix I to the primary prepolymer obtained in step S2 to keep the system temperature stable at the reaction temperature; after the dropping of premix I is completed, first keep the temperature at the reaction temperature for a period of time; then raise the temperature for a period of time; after the temperature - raising reaction time is completed, the predetermined product is obtained.
5. The preparation method of a hydrophobic fluorosilica microgel according to claim 4, characterized in that: In S1, the purity of perfluorooctylethyl acrylate is > 98%.
6. The preparation method of a hydrophobic fluorosilica microgel according to claim 4, characterized in that: In S1, the monofunctional monomer is methyl acrylate.
7. The preparation method of a hydrophobic fluorosilica microgel according to claim 4, characterized in that: In S1, the polyfunctional monomer is pentaerythritol triacrylate.
8. The preparation method of a hydrophobic fluorosilica microgel according to claim 4, characterized in that: The initiator in S1 is azobisisobutyronitrile.
9. The preparation method of a hydrophobic fluorosilica microgel according to claim 4, characterized in that: The solvent in S1 is butyl acetate.
10. The preparation method of a hydrophobic fluorosilica microgel according to claim 4, characterized in that: The addition amount of the solvent in S1 is 65% - 85% of the total mass.
Citation Information
Patent Citations
Method for preparing microgel resin and UV-cured contamination resistant coating prepared from microgel resin
CN101870760A